Copper(i)-catalyzed sulfonylation of (2-alkynylaryl)boronic acids with DABSO. Issue 6 (1st April 2016) - Mao, Runyu; Zheng, Danqing; Xia, Hongguang; Wu, Jie
Abstract : The scaffold of benzo[ b ]thiophene 1, 1-dioxides can be easily constructed through a copper(i )-catalyzed insertion of sulfur dioxide into (2-alkynylaryl)boronic acids. The reaction proceeds via insertion of sulfur dioxide and subsequent intramolecular 5- endo cyclization. Abstract : The scaffold of benzo[ b ]thiophene 1, 1-dioxides can be easily constructed through a copper(i )-catalyzed insertion of sulfur dioxide into (2-alkynylaryl)boronic acids. The reaction proceeds in the presence of 10 mol% copper(i ) acetate in DMF at 100 °C with high efficiency, leading to benzo[ b ]thiophene 1, 1-dioxides in good to excellent yields. The sulfonyl group can be easily introduced via insertion of sulfur dioxide and the subsequent intramolecular 5- endo cyclization affords the core of benzo[ b ]thiophene 1, 1-dioxide.